COVID-19 Return to Sport Toolkit (Sport Australia; Australian Institute of Sport, 2020)
Practical resources of Sport Australia that focus on giving sporting organisations a roadmap for the safest return to sport at all levels. The Toolkit builds on the AIS Framework for Rebooting of Sport and the Australian Government`s National principles for the resumption of sport and recreation activities and includes easy to use templates and step-by-step checklists for organisations to follow when planning their resumption of sporting activities. The Return to Sport Toolkit includes resources that can be used by all levels of Australian sport: - For National Sporting Organisations (NSOs), National Sporting Organisations for People with Disability (NSODs) and State Sporting Organisations (SSOs) recommencing their own training, competitions and programs; and - For participation programs and competitive sport (training and competition) conducted at local club and association level. COVID-19 Return to Sport Toolkit contains: - Detailed checklist for large and medium sporting orgaisations, - Simplified checklist for small sporting organisations, - COVID-19 safety coordinator, - COVID-19 satefty plan, - Sports trainer practices (for large, medium and small sporting orgaisations), - Attendance register (template), - COVID-19 hygiene guidance (communication manual).